PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 21 PEKANBARU - ', Pebrian; Daud, Damanhuri; ', Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems in this study is the low student learning outcomes in science lesson with the averages grade 65.47. This research aims to improve learning outcomes fifth grade science students of SDN 21 Pekanbaru with the implementation of cooperative learning model type Teams Games Tournaments. The study design used is a Class Action Research (PTK) is conducted in three cycles. Each cycle of four meetings teridiri namely penyampain material and tournaments and one time meeting daily tests. The research was conducted in September and October the number of 42 students consisting of 21 male and 21 female. In order to study this class action is successful, the researchers set the stage that action planning, action, observation, and reflection. The data collection instruments of observation and tests of learning outcomes. Technical analysis of the data that is used as follows, namely the activities of the Master, the average percentage of the activity the teacher first cycle was 68.77% with the category enough, on the second cycle increased to 73, 47% with the good category, then the third cycle increased again to 85.94% with a very good category. While the activities of the students, the average percentage of student activity in the first cycle was 67.21% with the category enough, on the second cycle increased to 78.15% with the good category, then the third cycle increased to 87.52% with the category of very good. Improved learning outcomes of the student base score is 65.47 increased to 70.11 (5%). In the daily deuteronomy I rise again in Deuteronomy Daily II to 77, 85 (21%) and increase again in deuteronomy daily III to 83.45 (36%). From this study be concluded that by applying the model of cooperative learning type Teams Games Tournaments (TGT) may improve learning outcomes fifth grade science students of SDN 21 Pekanbaru.Key Words: Cooperative Teams Games Tournaments, students,learning outcomes.